Farm Machinery Operation Cost Calculations - Kastens, Terry L. (My University, 1997)
This publication provides information so Kansas producers can be sustanible with their machinery operations.
MF2244_1997_05
Keywords: MF2244; Equipment and structures; Crops; MF